Faktor-Faktor yang mempengaruhi Harga Saham (Studi Empiris pada Perusahaan Perbankan tang terdaftar di Bursa Efek Indonesia Tahun 2020-2022) - Romadon, Ahmad Sahri; Mohklas, Mohklas (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2024)
This research aims to empirically test the influence of Return On Assets (ROA), Debt To Equity Ratio (DER) and Non Performing Loans (NPL) on Stock Prices (Empirical Study of Banking Companies Listed on the Indonesian Stock Exchange in 2020-2022). The population of this research is all banking companies listed on the Indonesian Stock Exchange in 2020-2022. The sample used in this research was 20 companies multiplied by 3 research periods with results of 60 respondents. This research uses a purposive sampling technique, namely a sampling technique that provides the opportunity to become a sample member with certain criteria. Then the data collection method is through questionnaires and data analysis using SPSS 25 which includes validity, reliability, classical assumption tests, multiple regression analysis, hypothesis testing using the t test and R2 test. The results of this research show that the independent variables, namely ROA and DER, have a positive and significant effect on share prices (Y), while NPL has a negative effect on stock prices. Based on the coefficient of determination value of 0.295, this means that 29.5 percent of the variation in share prices can be explained by 3 independent variables, namely ROA, DER, NPL. Meanwhile, the remaining 70.5 percent is explained by other variables. Keywords: ROA, DER, NPL, Share Price